1971
DOI: 10.1161/01.res.28.2.270
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Propranolol and Nicotinic Acid on the Inhibition of Plasma Free Fatty Acid Release in the Dog

Abstract: Fatty acid mobilization was effected in 24 anesthetized dogs by infusion of norepinephrine over a four-hour period. Infusions of propranolol and nicotinic acid at various doses, individually and in combination, were added and free fatty acid levels were serially determined. Synergistic action of the two agents was apparent in that minimally effective concentrations of the two agents when used in combination suppressed the release of free fatty acids to 29 percent of levels achieved with norepinephrine (1,186 j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
2007
2007

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…22 All these energy-sparing activities of beta-blockers may be augmented by the inherent negative inotropic qualities of the propranolol group of drugs.65 66 During the reperfusion period, the supply of energy is enhanced by beta-blocking drugs, which reduce inequalities of myocardial blood-flow distri-bution67 68 and limit microvascular injury during ischaemia.69 7I( The glucose extraction of the myocardium is increased and there is a peripheral antilipolytic action71 which reduces the rise in free fatty acids (FFA) usually associated with myocardial ischaemia36 72 and beta-adrenergic stimulation.' 73 High concentrations of FFA depress contractility and lead to arrhythmias.5 7 74 There is thus much theoretical rationale for the use of beta-blockade to miiinimise intraoperative ischaemic damage; we have confirmed this promise and have shown that though low-dose propranolol has a temporary effect on the heart during operation it does not impair postoperative contractility. We acknowledge gratefully the technical assistance of John Kitchen, AB McMillan, C Wilson, and Miss J Spoors, the statistical help of W Armstrong and A Murray, and the typing of Miss G Shaw and Miss V Jamieson.…”
Section: Discussionmentioning
confidence: 76%
“…22 All these energy-sparing activities of beta-blockers may be augmented by the inherent negative inotropic qualities of the propranolol group of drugs.65 66 During the reperfusion period, the supply of energy is enhanced by beta-blocking drugs, which reduce inequalities of myocardial blood-flow distri-bution67 68 and limit microvascular injury during ischaemia.69 7I( The glucose extraction of the myocardium is increased and there is a peripheral antilipolytic action71 which reduces the rise in free fatty acids (FFA) usually associated with myocardial ischaemia36 72 and beta-adrenergic stimulation.' 73 High concentrations of FFA depress contractility and lead to arrhythmias.5 7 74 There is thus much theoretical rationale for the use of beta-blockade to miiinimise intraoperative ischaemic damage; we have confirmed this promise and have shown that though low-dose propranolol has a temporary effect on the heart during operation it does not impair postoperative contractility. We acknowledge gratefully the technical assistance of John Kitchen, AB McMillan, C Wilson, and Miss J Spoors, the statistical help of W Armstrong and A Murray, and the typing of Miss G Shaw and Miss V Jamieson.…”
Section: Discussionmentioning
confidence: 76%